Clinical factors associated with baseline history of atrial fibrillation and subsequent clinical outcomes following initial implantable cardioverter‐defibrillator placement. Issue 6 (2nd May 2020) - Giancaterino, Shaun; Nishimura, Marin; Birgersdotter‐Green, Ulrika; Hoffmayer, Kurt S.; Han, Frederick T.; Raissi, Farshad; Ho, Gordon; Krummen, David; Feld, Gregory K.; Hsu, Jonathan C.
Abstract: Background: Atrial fibrillation (AF) is frequently present in patients with heart failure (HF) and an implantable cardioverter‐defibrillator (ICD). This study aims to identify clinical factors associated with a baseline history of AF in ICD recipients, and compares subsequent clinical outcomes in those with and without a baseline history of AF. Methods: We studied 566 consecutive first‐time ICD recipients at an academic center between 2011 and 2018. Logistic regression multivariable analyses were used to identify clinical factors associated with a baseline history of AF at the time of ICD implant. Cox‐proportional hazard regression models were constructed for multivariate analysis to examine associations between a baseline history of AF with subsequent clinical outcomes, including ICD therapies, HF readmission, and all‐cause mortality. Results: Of all patients, 201 (36%) had a baseline history of AF at the time of ICD implant. In multivariate analyses, clinical factors associated with a baseline history of AF included hypertension, valvular heart disease, body weight, PR interval, and serum creatinine level. After multivariate adjustment for potential confounders, a baseline history of AF was associated with an increased risk of anti‐tachycardia pacing (HR = 1.84, 95% CI = 1.19‐2.85, P  = .006), appropriate ICD shocks (HR = 1.80, 95% CI = 1.05‐3.09, P  = .032), and inappropriate ICD shocks (HR = 3.72, 95% CI = 1.7‐7.77, P  = .0001), but not other adverse outcomes. Conclusion: Among first‐time ICD recipients, specific clinical characteristics were associated with a baseline history of AF at the time of ICD implant. After adjustment for potential confounders, a baseline history of AF was associated with a higher risk of all ICD therapies in follow‐up.